Comparison of the Effect of Sertraline and Escitalopram on the Treatment of Major Depressive Disorder in Hemodialysis Patients: A Randomized Controlled Trial - Tahereh Sabaghian; Roya Vaziri-Harami; Seyed Alireza Ebadi; Minoo Heidari Almasi; Azadeh Ahmadi Koomleh; Amir Behnam Kharazmi; Ehsan Farhadi; Mahdiyeh Miri; Amir Ahmad Nassiri (Novelty in Biomedicine)
Background: We decided to compare the effects of sertraline and escitalopram in the treatment of major depressive disorder in hemodialysis patients.